2003
DOI: 10.1002/ardp.200300762
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Pharmacological Activities of 3, 5‐Dialkyl 1, 4‐Dihydro‐2, 6‐Dimethyl‐4‐Nitroimidazole‐3, 5‐Pyridine Dicarboxylates

Abstract: New analogues of nifedipine, in which the 2-nitrophenyl group at position 4 is replaced by a 1-methyl-5-nitro-2-imidazolyl substituent, were synthesized. The symmetrical dialkyl 1, 4-dihydro-2, 6-dimethyl-4-(1-methyl-5-nitro-2-imidazolyl)-3, 5-pyridinedicarboxylates were prepared by a classical Hantzsch condensation. The asymmetrical analogues were synthesized using a procedure reported by Iwanami that involved the condensation of alkylacetoacetate with methyl-, ethyl- or isopropyl3-aminocrotonate and 1-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The discovery of the DHP class of Ca 2+ channel blockers (CCBs) has represented a major therapeutic advance in treatment of cardiovascular disease such as hypertension, angina, and other spastic smooth muscle disorder (5–7). Recently, CCBs were identified as one of the first classes of drugs acting as MDR inhibitors (8–10).…”
mentioning
confidence: 99%
“…The discovery of the DHP class of Ca 2+ channel blockers (CCBs) has represented a major therapeutic advance in treatment of cardiovascular disease such as hypertension, angina, and other spastic smooth muscle disorder (5–7). Recently, CCBs were identified as one of the first classes of drugs acting as MDR inhibitors (8–10).…”
mentioning
confidence: 99%
“…nifadipine drug. [6][7][8][9][10][11][12][13] In continuation of this work we investigated the behaviour of 3aminocrotononitrile (1) towards some electrophilic reagents such as arylidenemalononitriles and arylidinecyanothioacetamides. Thus, it has been found that 3-aminocrotononitrile (1) reacted with arylidenmalononitriles 19a-c and arylidinecyanothioacetamides 19d,e to give dihydropyridine derivatives 24a-e. Establishing structure 24 was based on its spectral data and authentic specimen prepared from the reaction of 1 with the corresponding aldehydes derivatives 25a-e.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery that the 1,4‐dihydropyridine class of calcium channel antagonists inhibits Ca 2+ influx represented a major therapeutic advancement in the treatment of cardiovascular disease including hypertension, angina pectoris, and other spastic smooth muscle disorders (61–63). Moreover, some other biological applications were reported for DHPs making them a reliable class for widespread drug development (63–66).…”
Section: Dihydropyridinesmentioning
confidence: 99%